The Influence of Tv Show F.R.I.E.N.D.S. Toward English As Foreign Language (EFL) Students’ Speaking Skill - Eisya Dalila Nasution; Yulia Sari Harahap (Indonesian Journal of ELT and Applied Linguistics, 2025)
This study looks at how Friends, a television program, affects English as a Foreign Language (EFL) students' speaking abilities. The study uses qualitative analysis to show how regular comedy viewing improves spoken English confidence, vocabulary, pronunciation, and fluency. Friends offers an immersive learning experience that bridges the gap between academic knowledge and real-world application through its organic dialogues, colloquial language, and cultural situations. The main conclusions show that learners' oral ability is greatly enhanced by imitation strategies such mimicking the speech patterns of actors. The program also lessens speaking fear and promotes cultural knowledge. The study highlights the advantages of integrating real audio-visual materials, but it also points out drawbacks, like the necessity of choosing specific episodes to support learning objectives. The results support the thoughtful inclusion of TV shows.